Low-cost oral metronomic chemotherapy versus intravenous cisplatin in patients with recurrent, metastatic, inoperable head and neck carcinoma: an open-label, parallel-group, non-inferiority, randomised, phase 3 trial. Issue 9 (September 2020) - Patil, Vijay; Noronha, Vanita; Dhumal, Sachin Babanrao; Joshi, Amit; Menon, Nandini; Bhattacharjee, Atanu; Kulkarni, Suyash; Ankathi, Suman Kumar; Mahajan, Abhishek; Sable, Nilesh; Nawale, Kavita; Bhelekar, Arti; et al.
Summary: Background: Regimens for palliation in patients with head and neck cancer recommended by the US National Comprehensive Cancer Network (NCCN) have low applicability (less than 1–3%) in low-income and middle-income countries (LMICs) because of their cost. In a previous phase 2 study, patients with head and neck cancer who received metronomic chemotherapy had better outcomes when compared with those who received intravenous cisplatin, which is commonly used as the standard of care in LMICs. We aimed to do a phase 3 study to substantiate these findings. Methods: We did an open-label, parallel-group, non-inferiority, randomised, phase 3 trial at the Department of Medical Oncology, Tata Memorial Center, Homi Bhabha National Institute, Mumbai, India. We enrolled adult patients (aged 18–70 years) who planned to receive palliative systemic treatment for relapsed, recurrent, or newly diagnosed squamous cell carcinoma of the head and neck, and who had an Eastern Cooperative Oncology Group performance status score of 0–1 and measurable disease, as defined by the Response Evaluation Criteria In Solid Tumors. We randomly assigned (1:1) participants to receive either oral metronomic chemotherapy, consisting of 15 mg/m 2 methotrexate once per week plus 200 mg celecoxib twice per day until disease progression or until the development of intolerable side-effects, or 75 mg/m 2 intravenous cisplatin once every 3 weeks for six cycles. Randomisation was done by use of a computer-generated randomisation sequence, with a block size of four, and patients were stratified by primary tumour site and previous cancer-directed treatment. The primary endpoint was median overall survival. Assuming that 6-month overall survival in the intravenous cisplatin group would be 40%, a non-inferiority margin of 13% was defined. Both intention-to-treat and per-protocol analyses were done. All patients who completed at least one cycle of the assigned treatment were included in the safety analysis. This trial is registered with the Clinical Trials Registry-India, CTRI/2015/11/006388, and is completed. Findings: Between May 16, 2016, and Jan 17, 2020, 422 patients were randomly assigned: 213 to the oral metronomic chemotherapy group and 209 to the intravenous cisplatin group. All 422 patients were included in the intention-to-treat analysis, and 418 patients (211 in the oral metronomic chemotherapy group and 207 in the intravenous cisplatin group) were included in the per-protocol analysis. At a median follow-up of 15·73 months, median overall survival in the intention-to-treat analysis population was 7·5 months (IQR 4·6–12·6) in the oral metronomic chemotherapy group compared with 6·1 months (3·2–9·6) in the intravenous cisplatin group (unadjusted HR for death 0·773 [95% CI 0·615–0·97, p=0·026]). In the per-protocol analysis population, median overall survival was 7·5 months (4·7–12·8) in the oral metronomic chemotherapy group and 6·1 months (3·4–9·6) in the intravenous cisplatin group (unadjusted HR for death 0·775 [95% CI 0·616–0·974, p=0·029]). Grade 3 or higher adverse events were observed in 37 (19%) of 196 patients in the oral metronomic chemotherapy group versus 61 (30%) of 202 patients in the intravenous cisplatin group (p=0·01). Interpretation: Oral metronomic chemotherapy is non-inferior to intravenous cisplatin with respect to overall survival in head and neck cancer in the palliative setting, and is associated with fewer adverse events. It therefore represents a new alternative standard of care if current NCCN-approved options for palliative therapy are not feasible. Funding: Tata Memorial Center Research Administration Council. Translations: For the Hindi, Marathi, Gujarati, Kannada, Malayalam, Telugu, Oriya, Bengali, and Punjabi translations of the abstract see Supplementary Materials section.